Pengaruh Perbandingan Buah Apel Manalagi (Malus sylvestris) Dan Buah Naga Merah (Hylocereus polyrhizus) Terhadap Karakteristik Selai Lembaran - Hari, Apriani Kartini; Arihantana, Ni Made Indri Hapsari; Darmayanti, Luh Putu Trisna (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 14 No 2 (2025): Jurnal ITEPADO - 10.24843/itepa.2025.v14.i02.p01, 2025)
Sheet jam is a modification of spreadable jam into a solid, non-sticky sheet form. The food material to be processed into sheet jam is Manalagi apples, which have high pectin content but lack attractive color. Therefore, red dragon fruit is used to enhance the color and antioxidant activity. This study aims to determine the effect of the ratio of Manalagi apples and red dragon fruit on the characteristics of sheet jam and to determine the optimal ratio to produce sheet jam with the best characteristics. The experimental design used in this study was a Completely Randomized Design with 6 treatment levels of Manalagi apple and red dragon fruit ratios: 100:0, 85:15, 70:30, 55:45, 40:60, and 25:75. All treatments were repeated 3 times, resulting in 18 experimental units. The data were analyzed using analysis of variance, and if the treatment showed a significant effect, it was followed by Duncan's Multiple Range Test. The results showed that ratio of 55 percent Manalagi apples and 45 percent red dragon fruit had the best characteristics with water content of 23.26 percent, pH 4.28, total dissolved solids of 34.43 percent Brix, antioxidant activity of 80.63 percent, colour was liked with purplish red criteria, aroma was slightly liked, taste was liked, texture was liked and overall acceptance was liked. Keywords: Sheet jam, Manalagi apples, red dragon fruit